Responder por exclusão na aprendizagem de relações simbólicas envolvendo adjetivos - Ribeiro, Thaís Arantes (Universidade Federal de São Carlos, 2013)
Exclusion responding has been considered one of the processes by which children learn to relate new words to objects. This pattern of responding is usually tested with a matching to sample task. The goal of the present experiment was to verify if exclusion responding also occurs with properties-object relations: dictated model stimuli were adjectives (/happy/, /sad/ and /anger/) and comparison stimuli were properties of objects (dolls facial expression). A second goal was to investigate the relation between the quantity of exclusion trials and a learning outcome. Phase 1 established a baseline of auditory-visual discriminations in a natural situation with dolls; Phase 2 established the baseline among dictated words and pictures of the doll (a girl) with a specific software presented with a notebook; Phase 3 consisted of exclusion probes in which the pseudo words /piva/ and /fobam/ were presented as models in different trials and a defined face (related to baseline words), an undefined face (not related to baseline words) and a mask (blank comparison) were presented as comparison. Selection of undefined face showed exclusion control. Phase 3 also consisted of presentation of learning probes. In Phase 4 experimental blocks presented as comparison stimuli figures of another doll (boy) expressing the same emotions of the doll of Phase 3. The purpose of Phase 4 was to evaluate generalization of the results obtained in Phase 3. Experiment was finished if the participant had responded correctly the three learning probes or if he or she had been exposed to 10 exclusion trials with each relation. Data was collected with 22 typically developing preschool children between 24 and 29 months of age. All participants responded by exclusion along the experiment. 11 of the 22 participants showed a learning outcome, responding correctly the three learning probes (100% of correct responses) with one of the taught relations in Phase 3 or with one of the tested relations in Phase 4. Data confirm and extend regularity of exclusion responding. The amount of exclusion trials necessary to obtain a learning outcome and the best learning probes to be used still needs to be investigated.
Learning symbolic relations (word-qualifiers) by exclusion
Keywords: Psicologia experimental; Aprendizagem relacional; Responder por exclusão; Aquisição de vocabulário; Mapeamento rápido; Crianças; Relational learning; Vocabulary acquisition; Exclusion; Fast mapping; Children; CIENCIAS HUMANAS::PSICOLOGIA